Effects of edible antimicrobial coating on the safety and quality of fresh-cut solo papaya (carica papaya L.) - Marcelino, Angelica O. (College of Home Economics, 2010)
ABSTRACT The effects of antimicrobial coating on the quality of fresh-cut Solo papaya (Carica papaya L.) were investigated. The Solo papaya were asceptically cut and were subjected to various treatment combination of citric acid (0-0.5%) and carrageenan (0-0.5%) and stored at 2 to 6 °C. Physicochemical and microbial properties of the samples were monitored at d 0 and d 4. Consumer acceptance test using randomly selected 35 panelists was done at d 0. Given the results of aforementioned tests, standardization of chosen treatment combination was followed. Treated samples showed favorable results in terms of quality and safety compared to untreated samples. The combination of citric acid and carrageenan showed significant (p<0.05) effects on the pH, color and yeast and mold count of the Solo papaya. Coating solution of 0.1% carrageenan with either 0.1% or 0.5% citric acid both exhibited desirable results with the latter showing better output. The sample treated with this solution showed significantly (p<0.05) lower pH, higher L* values and chromacity compared to the samples dipped in 0.1% carrageenan with 0.1% citric acid. On the other hand, yeast and mold counts (YMC) and aerobic plate count (APC) did not vary between the two treatments. Likewise, treatments did not significantly (p>0.05) alter the acceptance of the samples. Coating solution of 0.1% carrageenan with 0.5% citric acid was subsequently standardized. No significant difference (p>0.05) was found among the three process treatment runs in terms of the tested safety and quality parameters. The antimicrobial coating solution of 0.1% carrageenan with 0.5% citric acid improved some of the physicochemical parameters, effectively reduced the initial and final microbial load and did not alter the sensory acceptance of the fresh-cut Solo papaya slices.